MARKET INTEGRATION AND PRICE TRANSMISSION OF BEEF IN THE ARCHIPELAGIC STATE: THE CASE OF THE PROVINCES IN INDONESIA - Elifas Omega Yusufadisyukur; Stephan von Cramon-Taubadel; Suharno; Rita Nurmalina (Jurnal Manajemen & Agribisnis, 2020)
The Archipelagic state condition brings challenges to market integration and price transmission on two provinces market pairs within and between the island. The duration of price correction is essential to ensure market integration. Therefore, this study aims to assess the integration of domestic markets for beef within an island and between the island and analyze the speed of adjustment (the correction) of the prices by two provinces within the island and between the islands. These aims, daily frequency (weekdays) of Beef Consumer Prices (BCP) of 4 types of beef (Primary Cut, Secondary Cut AB, Meat Manufacturing and Fancy and Variety Meat) from 01 January 2015 to 27 April 2018 containing 28,611 observations were obtained. The data were analyzed using the Vector Error Correction Model (VECM). This study reveals that the island's provinces have fewer integrated than the pairs provinces located between islands by comparing 31 pairs with 38 pairs. It can be concluded that from research, the price correction in the pairwise province within an island is stronger than the pairwise between the islands, with 10.33 % per day and 9.87 % per day, respectively. This study recommends the government to formulate policies that carry out equitable development, especially those that facilitate access to the central beef production in Indonesia to avoid market exploitation and spread price information along with provinces in Indonesia, especially in eastern Indonesia. Keywords: archipelagic state, market integration, Indonesia, beef, VECM